Hygiene behaviors and nutritional status of children living in orphanages in Bangladesh - Islam, Mohammad Shamsal; M. Yahya, Fazle Siddique; Ashraf, M. Mahfuz; Hossain, Mohammad Iqbal (International Journal Of Community Medicine And Public Health, 2023)
Background: Malnutrition is considered a complicated public health issue and depends on multiple factors. Hygienic behavior is related to orphan children’s growth, nutritional outcomes, and sound health. The study’s aim was to assess the hygiene behaviors and nutritional status of orphan students in Bangladesh. Methods: A descriptive cross-sectional quantitative study was conducted in three orphanage centers. A total of 120 respondents were interviewed. A descriptive analysis of the collected data was performed. Results: The monthly mean and median expenditure of orphans was 2000±475 BDT (20$). The number of toilets and waiting time for the orphan to use them are closely associated (χ2= 33.38; Cramer’s V=0.44, df=13; Sig; p<0.001). On average, an orphan waits 32.20 minutes to use the toilet facility when they need it. Orphan family income and disposal of waste in the toilet of the orphan center are strongly associated (χ2=99.19; Cramer’s V=0.49, df=39; Sig; p<0.001). There was a significant association between attending toilet-related hygiene and types of diseases. Hair fall, muscle wasting, fever, and xerosis of the skin were common diseases among orphans. Types of diseases orphans and schedule for the dietary chart are strongly associated (χ2=23.35; Cramer’s V=0.37, df=24; Sig; p<0.001). Conclusions: Integrated approach is required to counter the extent of malnutrition among orphans. Teachers of orphanages should receive proper training so that they are able to take care of the physical and mental health of the orphan children.